Epidemiology and Burden of Sleep Disturbances in Atopic Dermatitis in US Adults. (5th November 2022) - Silverberg, Jonathan Ian; Chiesa-Fuxench, Zelma; Margolis, David; Boguniewicz, Mark; Fonacier, Luz; Grayson, Mitchell; Simpson, Eric; Ong, Peck
Abstract : Background: The relationship between atopic dermatitis (AD) severity, sleep disturbance (SD), and health-related outcomes is not fully elucidated. Objective: The aim of the study was to determine the prevalence of SD in adult AD and its relationship with AD severity and health outcomes among the US population. Methods: A cross-sectional, US population–based survey study of 2893 adults was performed. Results: Among adults meeting the UK Diagnostic Criteria for AD, 255 (40.7%) reported 1 or more, 67 (11.1%) reported 3 to 4, and 57 (9.5%) reported 5 to 7 nights of SD in the past week; 475 (79.7%) reported at least some trouble sleeping in the past 3 days. Moderate and severe Patient-Oriented Scoring AD, Patient-Oriented Eczema Measure, and Numeric Rating Scale–itch and Numeric Rating Scale–skin pain scores were associated with more severe SD compared with those without AD. More frequent and severe SDs were associated with higher Dermatology Life Quality Index, lower 12-item Short-Form Health Survey, and higher Hospital Anxiety and Depression Scale (HADS) scores. Significant mediation by SD severity was observed between Patient-Oriented Eczema Measure and Numeric Rating Scale–itch with Dermatology Life Quality Index, 12-item Short-Form Health Survey physical and mental component scores, HADS-anxiety and HADS-depression scores, diagnosed anxiety, and heart disease. Conclusions: Atopic dermatitis and AD severity are associated with SDs. Sleep disturbances considerably impact quality of life and other health outcomes in adults with AD.